A study on teacher attitudes towards computer skill in the selected secondary school in Melaka / Mohd Faisal Sabuddin...[et al] - Sabuddin, Mohd Faisal (Faculty of Business and Management, 2013)
Tills study is carried out to identify whether teachers of different backgrounds differ in their computer skills level and at the same time to identify whether there is a correlation between teachers' attitudes and their computer skills. The fmal objective of this study is to investigate which attitude (anxiety, confidence, interest, or perceived usefulness) has a greater influence on the teachers' computer skills. All the teachers from the four different types of schools in Melaka Tengah area were chosen as samples. Pearson Correlation were used to analyze the data. The study showed that there was moderate relationship between the perceived usefulness of computer with their computer skills. In addition, the findings also revealed that there was a significant correlation between the computer positive attitudes which are interest and anxiety with the teachers' computer skills. The correlation analysis showed that there was a relationship between all teachers' attitudes which are computer interest, anxiety, confidence and perceived usefulness towards the teachers' computer skills. However, we found that teachers' interest in using the computer had a greatest correlation than other attitudes.